Utilización del gen Alt a 1 para la detección de Alternaria spp. en productos hortofrutícolas mediante una técnica de PCR - Martín de Santos, R.; García Lacarra, T.; Pavón Moreno, M. A. (Revista Complutense de Ciencias Veterinarias, 2008)
A polymerase chain reaction (PCR) method, based on oligonucleotide primers targeting the Alt a 1 gene, has been developed for the specific identification of Alternaria spp. In vegetables. The limit of detection of the method was 102 cfu/ml either in culture or tomato paste.